Pemanfaatan Limbah Plastik Menjadi Bahan Bakar Minyak - Fahri Husaini; Abdullah Syafri; Rizky Setyawan; Khairul Akmal Rambe; Muhammad Rafly Akbar; Bima Aditya Ramadhan (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
Plastic waste is a type of inorganic waste that takes around 50-80 million years to decompose in the soil. Plastic waste contributes to 90% of the waste in the ocean, causing damage to coastal ecosystems and having implications for the degradation of coastal ecosystems. To overcome this, the Mayor of Bontang has prepared a legal product that regulates the use of plastic waste and one of the efforts the author has made to tackle plastic waste in Bontang City is to create a tool that can convert plastic waste into fuel oil. The aim of this research is to determine the process of utilizing plastic waste into fuel oil and to determine the volume of fuel oil produced from processing plastic waste. This research is experimental research using the pyrolysis method. The trial results of processing plastic waste into fuel oil show that: the technology that is practically used is using the slow pyrolysis method with simple tools, the use of plastic waste into fuel oil is very effective to implement. Meanwhile, the volume of fuel oil for 1.4 kg is 350 ml at a temperature of 225℃ with a residence time of 4 hours. However, if the temperature is increased to 400-600℃, it is likely that the oil produced will increase.